Egg-laying by female Aedes aegypti shapes the bacterial communities of breeding sites - Mosquera, Katherine D. (2023)
Background: Aedes aegypti, the main arboviral mosquito vector, is attracted to human dwellings and makes use of human-generated breeding sites. Past research has shown that bacterial communities associated with such sites undergo compositional shifts as larvae develop and that exposure to different bacteria during larval stages can have an impact on mosquito development and life-history traits. Based on these facts, we hypothesized that female Ae. aegypti shape the bacteria communities of breeding sites during oviposition as a form of niche construction to favor offspring fitness. Results: To test this hypothesis, we first verified that gravid females can act as mechanical vectors of bacteria. We then elaborated an experimental scheme to test the impact of oviposition on breeding site microbiota. Five different groups of experimental breeding sites were set up with a sterile aqueous solution of larval food, and subsequently exposed to (1) the environment alone, (2) surface-sterilized eggs, (3) unsterilized eggs, (4) a non-egg laying female, or (5) oviposition by a gravid female. The microbiota of these differently treated sites was assessed by amplicon-oriented DNA sequencing once the larvae from the sites with eggs had completed development and formed pupae. Microbial ecology analyses revealed significant differences between the five treatments in terms of diversity. In particular, between-treatment shifts in abundance profiles were detected, showing that females induce a significant decrease in microbial alpha diversity through oviposition. In addition, indicator species analysis pinpointed bacterial taxa with significant predicting values and fidelity coefficients for the samples in which single females laid eggs. Furthermore, we provide evidence regarding how one of these indicator taxa, Elizabethkingia, exerts a positive effect on the development and fitness of mosquito larvae. Conclusions: Ovipositing females impact the composition of the microbial community associated with a breeding site, promoting certain bacterial taxa over those prevailing in the environment. Among these bacteria, we found known mosquito symbionts and showed that they can improve offspring fitness if present in the water where eggs are laid. We deem this oviposition-mediated bacterial community shaping as a form of niche construction initiated by the gravid female.